1981
DOI: 10.1083/jcb.91.1.157
|View full text |Cite
|
Sign up to set email alerts
|

Influence of collagen gel on the orientation of epithelial cell polarity: follicle formation from isolated thyroid cells and from preformed monolayers.

Abstract: The influence of collagen gels on the orientation of the polarity of epithelial thyroid cells in culture was studied under four different conditions . (a) Isolated cells cultured on the surface of a collagen gel formed a monolayer. The apical pole was in contact with the culture medium and the basal membrane was attached to the substratum .(b) Isolated cells embedded inside the gel organized within 8 d into follicles . The basal pole was in contact with collagen and the apical pole was oriented towards the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
106
0

Year Published

1982
1982
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(116 citation statements)
references
References 40 publications
10
106
0
Order By: Relevance
“…The inverted thyroid follicles cultured inside collagen gel revert to normal follicles (CHAMBARD et al, 1981(CHAMBARD et al, , 1984, or form compact spheroids with small lumina (GARBI et al, 1986). In all cases, including our results, the cell surfaces in contact with collagen lose microvilli and turn basal.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…The inverted thyroid follicles cultured inside collagen gel revert to normal follicles (CHAMBARD et al, 1981(CHAMBARD et al, , 1984, or form compact spheroids with small lumina (GARBI et al, 1986). In all cases, including our results, the cell surfaces in contact with collagen lose microvilli and turn basal.…”
Section: Discussionsupporting
confidence: 55%
“…The cell surface which is in contact with collagen shows characteristics of the basal pole, as CHAMBARD et al (1981) reported. RoDRIGUEZ-BoULAN and his co-workers (1983) reported that the cell-collagen contact triggers the polarized budding of viruses when Madin-Darby canine kidney (MDCK) cells are infected with enveloped viruses such as influenza and vesicular stomatitis viruses.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Porcine thyroid cells were isolated from fresh thyroid glands by discontinuous trypsin-EGTA treatment (Chambard et al 1981). Inside-out follicles were obtained as described previously (Espanet et al 1992, Giraud et al 1997.…”
Section: Cell Culturesmentioning
confidence: 99%
“…All these studies have succeeded in making reversed follicles by digestion of interfollicular connective tissue elements, which are considered to be an important factor in keeping cell polarity. CHAMBARD et al (1981) reported that the interaction of the cell membrane with extracellular components having adhesive properties appears to be a determinant factor in the orientation and stabilization of epithelial cell polarity.…”
Section: Discussionmentioning
confidence: 99%